Survival and prognostic factors following pulmonary metastasectomy for sarcoma - Marulli, Giuseppe (J Thorac Dis, 2017)
Sarcomas are a heterogeneous group of malignancies with a marked propensity to metastasize to the lungs. Chemotherapy offers only a limited benefit in metastatic disease, whereas lung metastasectomy, in selected cases, can lead to long-term survival. Other local ablative techniques and hybrid therapies have been proposed. A multidisciplinary setting is of paramount importance for choosing the most appropriate treatment for each case. There is no randomized controlled trial providing formal evidence of the effectiveness of lung metastasectomy. Main areas of controversy concern the selection of surgical candidates, the operative approach and the role of chemotherapy. Five-year survival rates range from 15% to 50.9%, as reported mainly in retrospective case-series in which several prognostic factors were identified. In this article, the authors review the surgical management of sarcoma metastases to the lung, with a particular focus on the outcomes and prognostic factors associated with long-term survival after resection. The role of chemotherapy and other adjunctive therapies is also discussed.